Analysis of Students’ Thinking Processes in Solving Mathematical Problems Based on Bruner’s Theory in Pythagorean Theorem Tasks - Wiranugraha, M. Eza; Theis, Roseli; Iriani, Dewi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study aims to describe and analyze the thinking processes of junior high school students in solving mathematical problems based on Bruner's theory in the context of the Pythagorean theorem. The study was conducted at SMP Negeri 7 Kota Jambi in May 2025. Data were collected through classroom observations as preliminary data, followed by questionnaires and problem-solving tests as primary data, and interviews as supporting data. All data were analyzed qualitatively. The findings show that at the enactive stage, most students demonstrated low performance; four students were categorized as poor, one as excellent, and one as good. At the iconic stage, student performance ranged from low to adequate, with one student rated excellent, two rated adequate, and three rated poor. At the symbolic stage, most students demonstrated high performance, with three students rated excellent, two rated good, and one rated poor. These results indicate that although students generally succeed at the symbolic stage, weaknesses at the enactive and iconic stages suggest that their understanding remains predominantly procedural rather than conceptual. Teachers are encouraged to apply learning strategies that intentionally strengthen all three of Bruner’s representational stages, rather than moving directly to symbolic reasoning without first providing concrete experiences and visual representations. Teachers should also consider students’ diverse thinking processes when designing instruction. Future studies should include larger samples and more diverse methods, such as quantitative or mixed-methods approaches, to further examine how representation-based strategies influence students’ mathematical problem-solving performance.